MANAGEMENT OF FLOATING WASTE AROUND THE KAHAYAN RIVERBANKS, PALANGKA RAYA - Ariyani; Ludang, Yetrie; Permana Kamis, Indrawan; Haryono, Agus; Amelia, Vera; Firlianty (Acta Scientiae et Intellectus, 2024)
Plastic waste floating in the waters can come from land or land activities. Plastic products used in everyday life can be in the form of packaging products, household appliances, transportation equipment parts, construction materials, electrical equipment, industry, textiles, and others. These plastic products will experience a decrease in quality under certain conditions and periods of use so that they become waste. The position of Palangka Raya City which was built from the edge of the Kahayan River is a problem in itself, especially for residents who live on the banks of the Kahayan River who throw garbage into the river. Changes in perception are needed to change people’s behavior towards waste. The act of littering will increase if there are no strict sanctions given to trash, even though the arrangement of facilities provided is adequate. Environmental care behavior raised by the community is closely related to environmental education that each individual gets.